Influence of Mix Properties of Concrete Slabs on Performance of Airport Pavements. Issue 1 (13th February 2020) - Park, Hae-Won; Kim, Dong-Hyuk; Lee, Jong-Hoon; Yum, Woo-Sung; Jeong, Jin-Hoon
Abstract : This study suggests improved criteria for the material properties and mix proportions of concrete slabs to enhance the performance of concrete pavement at Incheon International Airport (IIA) in Korea. Gimpo International Airport and Gimhae International Airport were selected for comparison with IIA based on their facility status and annual flight processing capability. These airports have the second and third largest annual numbers of flights per unit area of runway next to IIA. The criteria for aggregate and mix proportions were chosen for improvement because of durability cracks due to the poor quality of the aggregates and repeated freeze and thaw cycles, which are the major forms of distress in IIA. The mix specifications of the concrete slab of IIA showed lower contents of cement and liquid admixture, a higher abrasion rate of coarse aggregate, and a larger content of fines in the aggregate compared to other airports. Based on the comparison results, improved criteria were established. Concrete specimens were fabricated using the improved criteria, and the performance of the concrete pavement was evaluated by testing the air content and freeze-thaw resistance for 12 mix cases with different contents of cement, liquid admixture, and fines in the aggregate.